2020
DOI: 10.1049/hve.2019.0219
|View full text |Cite
|
Sign up to set email alerts
|

Influence regularity of O 2 on dielectric and decomposition properties of C 4 F 7 N–CO 2 –O 2 gas mixture for medium‐voltage equipment

Abstract: Fluorinated nitrile (C 4 F 7 N) gas mixture has been introduced as the most promising candidate to replace sulfur hexafluoride using in gas-insulated equipment. In this study, the authors explored the influence of oxygen on the dielectric and decomposition properties of C 4 F 7 N-CO 2-O 2 gas mixture. The authors found that the dielectric strength of the C 4 F 7 N-CO 2-O 2 gas mixture with 2, 4, 6, 8 and 10% O 2 was increased by 4.85%, 6.49%, 7.70%, 3.21% and 2.74% compared with C 4 F 7 N-CO 2. The addition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 39 publications
(52 reference statements)
0
21
0
Order By: Relevance
“…Without oxygen no complex formation was observed. It was described in recent publications that addition of oxygen has some positive effects on the properties of nitrile 1 containing gas mixtures (especially improvement of dielectric strength, avoidance of soot formation, and reduction of some gaseous decomposition products) , . However, due the possible formation of complex 2 , it is recommended to use as low oxygen concentrations as possible, considering parameters like the expected electrical arcing load.…”
Section: Resultsmentioning
confidence: 99%
“…Without oxygen no complex formation was observed. It was described in recent publications that addition of oxygen has some positive effects on the properties of nitrile 1 containing gas mixtures (especially improvement of dielectric strength, avoidance of soot formation, and reduction of some gaseous decomposition products) , . However, due the possible formation of complex 2 , it is recommended to use as low oxygen concentrations as possible, considering parameters like the expected electrical arcing load.…”
Section: Resultsmentioning
confidence: 99%
“…C 3 F 7 CN/N 2 mixtures may have black matter precipitation on the electrode surface after multiple discharge and breakdown, which has been confirmed in the several researches above. However, researchers found that adding a small amount of O 2 can inhibit the precipitation of solid matter such as carbon [44, 45]. Adding O 2 to C 3 F 7 CN/N 2 mixtures will promote the decomposition of C 3 F 7 CN, and produce oxygen‐containing decomposition products, including CO 2 and COF 2 [44].…”
Section: Gas Decomposition Properties and Compatibility With Solid mentioning
confidence: 99%
“…However, researchers found that adding a small amount of O 2 can inhibit the precipitation of solid matter such as carbon [44, 45]. Adding O 2 to C 3 F 7 CN/N 2 mixtures will promote the decomposition of C 3 F 7 CN, and produce oxygen‐containing decomposition products, including CO 2 and COF 2 [44]. Considering the influence of O 2 on the insulation performance of the C 3 F 7 CN/N 2 gas mixture, C 3 F 7 CN/N 2 added with 4–6% volume fraction O 2 shows certain improvement [45] whereas C 3 F 7 CN/CO 2 /O 2 added with 2–6% volume fraction of O 2 has a certain inhibition effect on the production of discharge by‐products [44].…”
Section: Gas Decomposition Properties and Compatibility With Solid mentioning
confidence: 99%
“…Actually, it is difficult to make a correct judgment of the fault severity based on the yield of the decomposition products, thus the gas production rate must be considered. The effective gas production rate can directly reflect the magnitude of energy consumed by the fault, the severity and development process of the fault [13]. As defined in equation 1, Ri is the absolute gas production rate, Ci1 and Ci2 denote the contents (ppm or peak area) of component i measured at the first and second times respectively, t  represents the time interval between the two tests.…”
Section: Cmentioning
confidence: 99%
“…On the other hand, POF also induces decomposition of gas insulating medium to generate various by-products. For example, several by-products such as H2S, SO2, SOF2, SO2F2 can be found to be used as operation state assessment components for GIE with SF6 as insulating medium [13]. GIE with C4F7N gas mixture as insulating medium can also be monitored and diagnosed by detecting the characteristic decomposition products.…”
Section: Introductionmentioning
confidence: 99%